The use of pattern in CORBA middleware : XML-Acceptor pattern / Norliana Muhammad - Muhammad, Norliana (2005)
The emerging of numerous systems required the available implementation of middleware to suite the different of application systems. Middleware is a software layer which allows different systems to communicate without bother about the platform of operating systems, programming language and the networks' protocol as well as the connection. Middleware like CORBA is useful and interoperability in order to send and reply back the requests from the different systems. The communication of the systems is well managed by using the pattern. The pattern provided in the research is XMLAcceptor pattern. The objectives of the research are to identify the benefits of using the pattern and the features of using XML-Acceptor Pattern with the CORBA middleware. Then, the weakness and strengthens of XML-Acceptor Pattern are provided. To achieve the objectives, the data and the information are gathered from the previous research through online and offline research. Besides that, the interview is conducted in formal and informal as well as via the electronic mail. Finally the results are produced where the XML-Acceptor pattern is simplicity, extensibility and richness pattern. The degree of both of the pattern and CORBA can work together is measured on the used of platform, hardware, software and the languages used by the systems. Besides that, the management of the data and the other object-oriented approach also has been considered. Developers are encourage to experiment the capability of the pattern and middleware before implement them through the Internet. This is because the challenges are there which included the security, the data management and safety and the time constraints. At the end of the research, there should be a lot of research will be done for better understanding in the future.